2008
DOI: 10.1016/j.clinph.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

The auditory P50 component to onset and offset of sound

Abstract: Objective: The auditory Event-Related Potentials (ERP) of component P 50 to sound onset and offset have been reported to be similar, but their magnetic homologue has been reported absent to sound offset. We compared the spatio-temporal distribution of cortical activity during P 50 to sound onset and offset, without confounds of spectral change. Methods: ERPs were recorded in response to onsets and offsets of silent intervals of 0.5 s (gaps) appearing randomly in otherwise continuous white noise and compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 67 publications
(115 reference statements)
4
16
0
Order By: Relevance
“…. No trial effects were anticipated (Gillette et al, 1997;MacDonald & Barry, 2014;Pratt, 2008) but an intensity effect was not ruled out (White & Yee, 2006). The P1 exhibited a vertex distribution with frontal enhancement consonant with previous accounts; no trial effect over the first 10 trials and no intensity interaction over trials 10 and 11 were found.…”
Section: Accepted Manuscriptsupporting
confidence: 77%
See 1 more Smart Citation
“…. No trial effects were anticipated (Gillette et al, 1997;MacDonald & Barry, 2014;Pratt, 2008) but an intensity effect was not ruled out (White & Yee, 2006). The P1 exhibited a vertex distribution with frontal enhancement consonant with previous accounts; no trial effect over the first 10 trials and no intensity interaction over trials 10 and 11 were found.…”
Section: Accepted Manuscriptsupporting
confidence: 77%
“…The P1 has been linked to stimulus onset and preattentive arousal and should be evoked by the first stimulus with no diminution over trials (Gillette et al, 1997 -Fz reference;MacDonald & Barry, 2014;Pratt, 2008), however some sensitivity to intensity change may be observed (White & Yee, 2006). The N1, sensitive to stimulus onsets/offsets (Näätänen, 1988;Näätänen & Picton, 1987), should not decrement over trials (Rushby & Barry, 2009;Barry et al, 2011Barry et al, , 2013, and increased intensity may yield greater responses (Näätänen & Picton, 1987;Polich, 1996).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…An alternative explanation is that this negativity represents an offset N1. Offset N1s have generally been observed to have a double peaked morphology with the first peaking more frontally at approximately 100 ms (thought equivalent to N1a) and the second peaking more centrally at approximately 150 ms (thought equivalent to N1b) after the tone cessation (Pratt, Bleich, & Mittleman, ; Pratt, Starr, Michalewski, Bliech, & Mittelman, ). Although the N2‐like component in the present study peaks a little later than might be expected (glide, loud, and frequency all peak at about 240–250 ms, which is 190 ms after tone offset with the exception of that to the long duration tone, which peaks at about 215 ms, about 95 ms after offset), offset N1s at latencies consistent with that observed here have been reported (Horvath, in press) and, moreover, have also been observed to complicate interpretation of apparent P3 effects in standard minus deviant difference waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…The auditory P50 component is the earliest (around 50 ms) and the smallest in amplitude of the auditory ERPs [134]. When normal controls are confronted by repetitive auditory stimuli, an inhibitory mechanism is activated to block out irrelevant, meaningless or redundant stimuli.…”
Section: P50 Sensory Gatingmentioning
confidence: 99%